THEME: COMPARATIVE ANALYSIS OF THE POLITICAL SYSTEMS OF THE UNITED KINGDOM AND UZBEKISTAN - Muhammadyunusova Marhabo Qodirjon qizi (TADQIQOTLAR, 2025)
Abstract This article analyzes the political systems of the United Kingdom and the Republic of Uzbekistan from both historical and functional perspectives. It compares the structures of government, legislative institutions, electoral systems, and political parties in both countries. The study highlights the similarities and distinctive features of each system and provides useful insights for students, researchers, and political analysts.